Mechanical properties of talc and calcium carbonate filled PVC - Bee, Soo Tueen (Ibnu Sina Institute for Fundamental Science Studies, UTM, 2007)
The main aim of this work was to compare the mechanical properties of calcium carbonate (CaCO3) and talc filled PVC. Talc and CaCO3 are common fillers in plastics such as PVC to reduce cost and modify mechanical properties. The PVC resin and additives were blended by using high speed laboratory mixer to produce a homogenized PVC formulation. Then, the dry blended samples were melted and sheeted on the two roll mill machine. The sheeted PVC compounds were compression moulded into impact and flexural test specimens. Flexural and impact tests were then performed to determine and compare the mechanical properties of both PVC composites. Talc filled PVC composite gave the highest flexural modulus but the lowest impact strength compared to all grades of CaCO3 filled PVC composites. The SM90 CaCO3 gave the most optimum properties in trems of impact strength and flexural modulus compared to all grades of CaCO3.